UPAYA PENINGKATAN HASIL BELAJAR SISWA DENGAN PENERAPAN KETERAMPILAN BERTANYA DENGAN TEKNIK MENUNTUN DAN MENGGALI KEMAMPUAN SISWA PADA MATERI POKOK KEGIATAN MANUSIA DAN MASALAH LINGKUNGAN KELAS X MADRASAH ALIYAH BARUMUN TENGA - Nasution, Nurhidayah Fithriyah (JURNAL EDUCATION AND DEVELOPMENT, 2016)
The aims of this research was to increase the studentâs learning outcomes by implementation of questioning skill using guiding and exploring technique of studentâs ability in Human Activities and Environment Problem Grade X Barumun Tengah. The research method was descriptive by direct observation to teacher (researcher) and studentâs observation. The research implementation was conducted by subject teacher where the type of the research was Class Action Research (PTK). The population of this research was the entire students Grade X consisted of two classes totalling 58 students.The sampling method was random sampling. The used instruments was test in the problem form of Human Activities and Environment Problem subject matter. The indicator of research success were the average value and mastery learning of students. The studentâs learning outcomes in cyclus I was 75.9 and the deviation standard was 10.47, the learning outcomes in cyclus II was 76.5 and the deviation standard was 9.3 and the learning outcomes in cyclus III was 84.6 and the deviation standard was 11.7. The studentâs mastery learning in cyclus I was 80.7% while 19.3% unfinished, the learning mastery in cyclus II was 88.5% while 11.5% unfinished, the learning mastery in cyclus III was 92.3% while 7.7% unfinished. Based on the research result can be concluded that learning by Implementation of Questioning Skill using Guiding and Exploring Technique of Studentâs Ability in Human Activities and Environment Problem Grade X Barumun Tengah can increase the Studentâs Learning Outcomes.